Impact of go green campaign on green behaviour intention among consumers in Klang Valley, Malaysia - Hosseinpour, Masoumeh (2014)
Go Green Campaigns are being widely implemented around the world to expose environmental issues to the public while raising awareness of the benefits of having a green behaviour on the environment. The Malaysian government has been promoting nationwide green behaviour in order to be on a par with the global green movement. At present Malaysia is going through a transformation to become a developed country. Both the government and the Non-Governmental Organisations (NGOs) have been asked to conduct Go Green Campaigns to inform and educate the public on the benefits associated with acquiring green behaviour. Huge funding is allocated for this purpose by the government and NGOs have been asked to publicise the environmental degradation and change people‟s behaviour towards a greener one. The Go Green Campaigns are on-going activities which have become a trend in Malaysia. However, their effectiveness on the public‟s intention towards adopting a green behaviour is debateable. Thus this study intends to uncover the underlying factors that could influence the intentions of the Klang Valley residents to change their behaviour toward acquiring green behaviour. For this purpose the Theory of Planned Behaviour was adopted as the theoretical framework of this study. In total, 1206 respondents were interviewed by completing a structural questionnaire which gathered information on their attitudes towards Go Green Campaigns as well as their intention to behave in an environmentally friendly way. Chi-square analysis was employed to determine whether there is a significant difference between socio-economic and demographic factors towards the awareness and existence of Go Green Campaigns in Malaysia and the notion of green behaviour. The result of the first chi-square analysis shows that most of the socio-economic and demographic factors such as gender, race, and educational level have significant differences with regards to awareness of the existence of Go Green Campaigns in Malaysia. For the second chi-square analysis, the results show that some of the variables such as gender, marital status, and income level have significant differences with the awareness and knowledge of the green behaviour concept. Exploratory Factor Analysis was used to uncover the underlying factors that could influence the intentions of the respondents to perform green behaviour. Four latent factors were identified as influencing respondents‟ intention to put environmentally friendly behaviour into action. The 4 factors comprise of concern for the society, motivation, environmental concerns, and the importance of performing green behaviour. Binary logistic model procedure was applied to determine the extent of selected socio-economic/demographic characteristics and attitudes and also factors that influence the intentions of respondents to perform green behaviour. The results indicated that, the demographic factors such as gender, marital status, residential area, income level, and educational background and factors such as concern for the society and the importance of performing green behaviour are relevant in explaining the respondent‟s intention to perform green behaviour. Go Green Campaigns have proven to be successful in increasing the intention of the respondents to change their behaviour towards protecting the environment. However, the concern for the society is one of the most important factors to influence the intention of the respondents to practice green behaviour. These types of campaigns are helpful in terms of making the public aware of the importance of the environment and how people can help to protect it by adopting green behaviour. Gender also plays a very important role towards the decision to change the behaviour. Though Go Green Campaigns are implemented nationwide, people living in urban areas and people with higher educational levels show a greater intention to perform green behaviour. This indicates that Go Green Campaigns can influence people from any social background to acquire the intention to behave in an environmentally friendly way. Furthermore, though most of the respondents had a positive point of view towards Go Green Campaigns, there were still some people with other opinions. Even though Go Green Campaigns could be successful in building intention of going green among people but, these programmes still need a lot of improvements. It is better to design a careful curriculum to develop better qualified campaigns to keep people interested in them. One should try to inform people who do not have information about the Go Green Campaigns, and also motivate those who are not yet interested. Moreover, the campaign organiser should try to find the reasons why there are some people with a negative point of view or no interest. Based on this one can provide a better programme to them.